New He-O-Sr-Nd isotopes and chronology of Quaternary lavas from the Kula volcanic field (western Türkiye): Implications for temporal changes in the magma source - Duru Cesur; Halim Mutlu; Ercan Aldanmaz; Finlay M. Stuart; Ana Carracedo; Robert M. Ellam; Nilgün Güleç (Chemical Geology, 2025)

Stream sediment and soil geochemistry of the largest volcanogenic massive sulfide deposit in Türkiye, Karaburun deposit (Central Pontides) - Buğra Çavdar; Kurtuluş Günay; Halim Mutlu (Journal of Geochemical Exploration, 2025)

Mineralogical, fluid inclusion, and stable isotope constraints on the genesis of Keban Pb Zn skarn deposit, southeast Anatolia - Ece Kırat; Halim Mutlu (Geochemistry, 2025)

Hydrogeochemical and isotopic characterization of the El-Tarf geothermal aquifer (Algerian−Tunisian border): Implications of the regional geodynamic structure and the water−rock interactions - Hana Nouali; Yasmina Bouroubi-Ouadfel; Adnane Souffi Moulla; Halim Mutlu; Orlando Vaselli; Haythem Dinar; Abdelkader Khiari (Journal of African Earth Sciences, 2025)

Geochemical and isotopic constraints on thermal waters around the Gulf of Edremit, western Türkiye - Hafize Akıllı; Önder Kayadibi; Halim Mutlu; Şule Gürboğa; Macit Karadağlar; Serap Arıkan; Sevilay Tan (Geothermics, 2025)

Helium and carbon isotope compositions of thermal fluids in the northeastern Anatolia: Implications for the heat source and volatile flux - Harun Aydin; Hüseyin Karakuş; Halim Mutlu; Nilgün Güleç (Chemical Geology, 2024)

Manifestations of Quaternary syn‐eruptive fluid circulations on carbonate veins, Central Anatolian Volcanic Province - Volkan Karabacak; Halim Mutlu; Kiymet Deniz (Journal of Quaternary Science, 2021)
In this study, we investigate the geochronological, geochemical and isotopic characteristics of two travertine sites surrounded by Quaternary eruption centres in central Anatolia with ample palaeo‐eruption records. High‐resolution carbonate precipitation records, revealed by U‐Th dating, are clustered around 5–35, 60–100 and 120–170 ka and are well correlated with the dataset on eruptions as well as the position of fractures related to the volcanic centres. Syn‐eruptive carbonate precipitation seems to occur due to the circulation of CO 2 ‐rich fluids along the extensional fracture systems aligned tangentially to the related volcanic conduit and, therefore, the study of this system could be an alternative technique for the reconstruction of palaeo‐eruptions. δ 18 O values of the studied travertines are within the range of meteogene fluids. Oxygen isotope compositions at around 130 ka match well with Glacial Termination II that is also recorded by climate proxies in various cave and benthic deposits throughout the world. It is likely that the studied carbonates were precipitated under similar fluid circulation conditions which are represented by a high rate of dilatation followed by a meteoric water influx into the extensional fractures.

Environmental and climatic signals from stable isotopes in Anatolian tree rings, Turkey - Halim Mutlu; Nesibe Köse; Ünal Akkemik; Duru Aral; Ali Kaya; Sturt W. Manning; Charlotte L. Pearson; Nüzhet Dalfes (Regional Environmental Change, 2012)

Geochemical Monitoring of Geothermal Waters (2002–2004) along the North Anatolian Fault Zone, Turkey: Spatial and Temporal Variations and Relationship to Seismic Activity - Selin Süer; Nilgün Güleç; Halim Mutlu; David R. Hilton; Candan Çifter; Mesut Sayin (Pure and Applied Geophysics, 2008)